2016
DOI: 10.1504/ijstructe.2016.073679
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced external progressive collapse mitigation scheme for RC structures

Abstract: This paper discusses enhancement of an external mitigating scheme to maximise the resistance of reinforced concrete continuous beams to progressive collapse due to interior support failure. The mitigating scheme using external unbounded fibre reinforced plastic straight cables and a relevant numerical model were presented by the authors in a published companion paper to predict the progressive collapse resistance of the mitigated beams. This study extends the previous work to efficiently enhance the resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Concrete follows a non-linear uniaxial constant confinement model [29][30][31]. Steel reinforcement (rebar) and steel angles for retrofitting (Section 4) were modeled with a simplified version of the Ramberg-Osgood model [30,31] cited by Elkholy & Ariss [32], using the software. The geotechnical survey displayed a high soil performance level, and therefore, the discussion of the performance of the building is centered on the structural non-compliances.…”
Section: Methodsmentioning
confidence: 99%
“…Concrete follows a non-linear uniaxial constant confinement model [29][30][31]. Steel reinforcement (rebar) and steel angles for retrofitting (Section 4) were modeled with a simplified version of the Ramberg-Osgood model [30,31] cited by Elkholy & Ariss [32], using the software. The geotechnical survey displayed a high soil performance level, and therefore, the discussion of the performance of the building is centered on the structural non-compliances.…”
Section: Methodsmentioning
confidence: 99%
“…Hao et al [31] and Shi et al [32] also employed explosive loads in their studies and proposed a new methodology for analyzing the behavior of RC frames under the progressive collapse scenario. Elkholy and El-Ariss [33][34][35][36] as well as El-Ariss and Elkholy [37] presented a system and modeling algorithm for strengthening RC statically indeterminate beams to resist progressive collapse due to internal column failure. External unbounded unstressed straight wires attached to the beam at deviator and anchorage locations were proposed as part of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…Although CL can be used to highlight the key load-transfer mechanisms, the results revealed that UDL is a better representative loading scheme for investigating the progressive collapseresistance of beam-slab sub-assemblages [38,39]. El-Ariss and Elkholy [40] and Elkholy and El-Ariss [41][42][43][44] presented a modeling procedure and strengthening arrangement for RC continuous members to withstand progressive failure as a result of a missing internal column. The method features external cables attached to the beam at constraint and holding locations without being stressed.…”
Section: Introductionmentioning
confidence: 99%